SCIENTIFIC AND PEDAGOGICAL FOUNDATIONS OF DEVELOPING LOGICAL THINKING IN FUTURE EDUCATORS (Scientific journal of the Fergana State University, 2025)
The article studies the theoretical and methodological foundations of developing logical thinking in future teachers, the methodology for developing logical thinking in future teachers based on interdisciplinary cooperation, the effectiveness of developing logical thinking in future teachers based on interdisciplinary cooperation. Also, The essence and theoretical foundations of the concept of logical thinking are analyzed.